Effects of adjuvant huaier granule therapy on survival rate of patients with hepatocellular carcinoma - Shi, Ke; Bi, Yufei; Zeng, Xuanwei; Wang, Xianbo (Frontiers in Pharmacology, 2023)
Objective: Clinical trials have reported that Huaier granule inhibits the recurrence of hepatocellular carcinoma (HCC) after resection. However, its efficacy in patients at different clinical stages of HCC remains unknown. We investigated the effects of Huaier granule on the 3-year overall survival (OS) rate of patients at different clinical stages of HCC. Design: This cohort study included 826 patients with HCC, screened between January 2015 and December 2019. The patients were divided into Huaier (n = 174) and control groups (n = 652), and the 3-year OS rates were compared between the two groups. To eliminate bias caused by confounding factors, propensity score matching (PSM) was performed. We used the Kaplan-Meier method to estimate OS rate and tested the difference using the log-rank test. Results: Multivariable regression analysis revealed that Huaier therapy was an independent protective factor for 3-year survival rate. After PSM (1:2), the Huaier and control groups comprised 170 and 340 patients, respectively. The 3-year OS rate was remarkably higher in the Huaier group than in the control group (adjusted hazard ratio [aHR]: 0.36; 95% confidence interval: 0.26–0.49; P < 0.001). The aHR for Huaier use for 3–12, 12–24, and > 24 months was 0.48, 0.23, and 0.16, respectively, indicating a dose-response pattern. For the 3–12-, 12–24-, and > 24-month groups, the 3-year OS rate was 54.1%, 68.6%, and 90.4%, respectively. Multivariate stratified analysis confirmed that the mortality risk in Huaier users was lower than that in non-Huaier users in most subgroups. Conclusion: Adjuvant Huaier therapy improved the OS rate in patients with HCC. However, these findings require further verification through prospective clinical studies.